The Split Second Effect: The Mechanism of How Equinus Can Damage the Human Foot and Ankle - Amis, James (Frontiers in Surgery, 2016)
We are currently in the process of discovering that many, if not the majority, of non-traumatic acquired adult foot and ankle problems are caused by a singular etiology: equinus or the isolated gastrocnemius contracture. There is no question that this biomechanical association exists and in time much more will be uncovered. There are three basic questions that must be answered: why would our calves tighten as we normally age, how does a tight calf, or equinus, actually cause problems remotely in the foot and ankle, and how do the forces produced by equinus cause each individual resulting specific pathology in the foot and ankle? The purpose of this paper is to address the second question: how does a tight calf mechanically cause problems remotely in the foot and ankle? There has been little evidence in the literature addressing the biomechanical mechanisms by which equinus creates damaging forces upon the foot and ankle and as a result a precise, convincing mechanism is still lacking. Thus the mere concept that equinus has anything to do with foot pathology is generally unknown or disregarded. The split second effect, described here, defines exactly how the silent equinus contracture creates incremental and significant damage and injury to the human foot and ankle resulting in a wide variety of pathological conditions. The split second effect is a dissenting theory based on 30 years of clinical and academic orthopaedic foot and ankle experience, keen clinical observation along the way, and review of the developing literature, culminating in examination of many hours of slow motion video of normal and abnormal human gait. To my knowledge, no one has ever described the mechanism in detail this precise.